2021
DOI: 10.3390/insects12090812
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterizations and Functional Analyses of LmR2D2 in the Locusta migratoria siRNA Pathway

Abstract: Small interfering RNAs (siRNAs) are non-coding RNAs with a length of 21~23 nucleotides (nt) and present in almost all eukaryotes. The formation of siRNA is a highly conserved post-transcriptional gene-silencing mechanism mediated by key proteins, including Dicer2, Argonaute2 (Ago2) and R2D2. R2D2 has been identified as a double-stranded RNA (dsRNA)-binding protein and reported as an integral component of the siRNA pathway in Drosophila. However, the involvement of R2D2 in the siRNA pathway of Locusta migratori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The procedure for protein extraction and purification was adapted from that described by Gao et al . (2021). In brief, the recombinant protein was purified using Ni‐NTA agarose beads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for protein extraction and purification was adapted from that described by Gao et al . (2021). In brief, the recombinant protein was purified using Ni‐NTA agarose beads.…”
Section: Methodsmentioning
confidence: 99%
“…After incubation at 16°C for 20 h, bacterial pellets were harvested by centrifugation. The procedure for protein extraction and purification was adapted from that described by Gao et al (2021). In brief, the recombinant protein was purified using Ni-NTA agarose beads.…”
Section: Expression and Purification Of A Truncated Recombinant Lmchc...mentioning
confidence: 99%
“…First, it functions upstream of RNAi to convert dsRNA to siRNA. Second, it functions downstream of RNAi for the formation of stable protein complexes (including Dicer2 and R2D2) after siRNA production, followed by mRNA shear [ 12 , 34 ]. The impact of dsRNA on the physiology of insects has also been studied in several species.…”
Section: Discussionmentioning
confidence: 99%
“…The siRNA-mediated RNAi pathway can be triggered by either endo-siRNAs generated from the transposon for genome transposon defence or exo-siRNAs generated from RNA viruses for viral defence or from experimentally introduced long dsRNAs [ 5 ]. These differences are important because the biogenesis and processing of miRNAs, endo-siRNAs and exo-siRNAs depend on different dsRBPs as Dicer binding partners [ 6 , 7 ]. Previous studies have shown that Loquacious (Loqs) and R2D2 [dsRNA-binding protein with two dsRNA-binding domains (R2) and ability to associate to Dicer−2 (D2)] are the dsRNA binding proteins involved in the RNAi pathways [ 8 ].…”
Section: Introductionmentioning
confidence: 99%